Multimedia Systems - Martirosyan, Robert (Toronto Academic Press, 2024)
This text covers the design, development, and implementation of multimedia applications and systems. The book explores various topics such as multimedia hardware and software, digital media representation and compression, multimedia communication, and multimedia databases. It is an essential resource for students and professionals in the field of multimedia, providing a thorough understanding of the principles and practices of multimedia systems. This book will equip you with the knowledge and skills needed to create and manage multimedia systems in a rapidly evolving technological landscape.